Pengembangan Model Klasifikasi Dokumen Artikel Teks Berita Olahraga dan Bukan Olahraga dalam Bahasa Indonesia Menggunakan Algoritma Support Vector Machine - Muhammad Alif Iman Aulia; Yulia Ery Kurniawati (UNIVERSITAS KALBIS, 2022)
The purpose of classification is to inform the machine (algorithm) of group division or in other words, teach the machine how to divide the group. The classification process uses the Support Vector Machine (SVM) method. SVM is used because it has a good reputation in the classification. This study aims to classify sports news and non-sports news using the SVM algorithm and with the addition of n-gram features and Term Frequent Inverse Document Frequency (TF-IDF). The results showed an accuracy of 92%.